The effect of nalidixic acid on growth and reproductive events in nucleocytosolic and chloroplast compartments in the alga Scenedesmus quadricauda - Zachleder, V; Kawano, S; Cepák, V; Kuroiwa, T (Folia microbiologica, 2004)
The courses of rRNA accumulation, DNA replication, and nuclear division were followed both in the chloroplast and the nucleocytosolic compartments during the cell cycle in synchronized populations of the chlorococcal alga Scenedesmus quadricauda. Control and nalidixic acid-treated cultures were compared. Nalidixic acid (150 mg/L) was added either at the beginning of the cell cycle or consecutively during the cell cycle to subcultures transferred into the dark. If the inhibitor was applied at the beginning of the cell cycle, chloroplast DNA did not replicate and nucleoids did not divide. Chloroplast division, however, was coordinated in a timely fashion with cytokinesis even under conditions of blocked chloroplast DNA replication. While the growth rate was slowed down, the courses of reproductive processes in the nucleocytosolic compartment were not affected and their timing and the number of rounds were coordinated with growth rate as in the control culture. The rate of cytosolic rRNA synthesis was lower but no apparent effect was seen on the amount of rRNA that accumulated during the cell cycle. In contrast, lower levels of chloroplast rRNA were found at the end of the cell cycle compared with the control culture. Experiments in which cells were transferred to the dark during the cell cycle showed that the inhibitor affected none of the reproductive events in the nucleocytosolic compartment. In the chloroplast compartment, DNA replication was inhibited in inhibitor-treated cultures, but was unaffected in controls. The chloroplast nucleoids themselves divided even in the presence of the inhibitor, reducing their DNA content to a level which corresponded to that in freshly formed control daughter cells.
Keywords: kyselina nalidixová; Scenedesmus; chloroplasty; Nalidixic Acid; Chloroplasts